Shape memory alloy actuated accumulator for ultra-deepwater oil and gas exploration. (14th March 2016) - Patil, Devendra; Song, Gangbing
Abstract: As offshore oil and gas exploration moves further offshore and into deeper waters to reach hydrocarbon reserves, it is becoming essential for the industry to develop more reliable and efficient hydraulic accumulators to supply pressured hydraulic fluid for various control and actuation operations, such as closing rams of blowout preventers and controlling subsea valves on the seafloor. By utilizing the shape memory effect property of nitinol, which is a type of shape memory alloy (SMA), an innovative SMA actuated hydraulic accumulator prototype has been developed and successfully tested at Smart Materials and Structure Laboratory at the University of Houston. Absence of gas in the developed SMA accumulator prototype makes it immune to hydrostatic head loss caused by water depth and thus reduces the number of accumulators required in deep water operations. Experiments with a feedback control have demonstrated that the proposed SMA actuated accumulator can provide precisely regulated pressurized fluids. Furthermore the potential use of ultracapacitors along with an embedded system to control the electric power supplied to SMA allows this accumulator to be an autonomous device for deployment. The developed SMA accumulator will make deepwater oil extraction systems more compact and cost effective.